Radiochemical and Biological Evaluation of 3p-C-NETA-ePSMA-16, a Promising PSMA-Targeting Agent for Radiotheranostics - Erika Murce; Stephen Ahenkorah; Savanne Beekman; Maryana Handula; Debra Stuurman; Corrina de Ridder; Frederik Cleeren; Yann Seimbille (MDPI AG, 2023)
Bifunctional chelators (BFCs) are a key element in the design of radiopharmaceuticals. By selecting a BFC that efficiently complexes diagnostic and therapeutic radionuclides, a theranostic pair possessing almost similar biodistribution and pharmacokinetic properties can be developed. We have previously reported 3p-C-NETA as a promising theranostic BFC, and the encouraging preclinical outcomes obtained with [18F]AlF-3p-C-NETA-TATE led us to conjugate this chelator to a PSMA-targeting vector for imaging and treatment of prostate cancer. In this study, we synthesized 3p-C-NETA-ePSMA-16 and radiolabeled it with different diagnostic (111In, 18F) and therapeutic (177Lu, 213Bi) radionuclides. 3p-C-NETA-ePSMA-16 showed high affinity to PSMA (IC50 = 4.61 ± 1.33 nM), and [111In]In-3p-C-NETA-ePSMA-16 showed specific cell uptake (1.41 ± 0.20% ID/106 cells) in PSMA expressing LS174T cells. Specific tumor uptake of [111In]In-3p-C-NETA-ePSMA-16 was observed up to 4 h p.i. (1.62 ± 0.55% ID/g at 1 h p.i.; 0.89 ± 0.58% ID/g at 4 h p.i.) in LS174T tumor-bearing mice. Only a faint signal could be seen at 1 h p.i. in the SPECT/CT scans, whereas dynamic PET/CT scans performed after administration of [18F]AlF-3p-C-NETA-ePSMA-16 in PC3-Pip tumor xenografted mice resulted in a better tumor visualization and imaging contrast. Therapy studies with short-lived radionuclides such as 213Bi could further elucidate the therapeutic potential of 3p-C-NETA-ePSMA-16 as a radiotheranostic.